2018
DOI: 10.1038/s41594-018-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of complex I from mouse heart mitochondria in two biochemically defined states

Abstract: Complex I (NADH:ubiquinone oxidoreductase) uses the reducing potential of NADH to drive protons across the energy-transducing inner membrane and power oxidative phosphorylation in mammalian mitochondria. Recently, cryoEM analyses have produced close-to-complete models of all 45 subunits in the bovine, ovine and porcine complexes, and identifed two states relevant to complex I in ischemia-reperfusion injury. Here, we describe the 3.3-Å structure of complex I from mouse heart mitochondria, a biomedically-relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
448
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(487 citation statements)
references
References 72 publications
(170 reference statements)
25
448
0
Order By: Relevance
“…In plant, 25 proteins shared with aerobic yeast or mammals are present. Similarly to the previously obtained complex I structure 4,6,9,16 , the supernumerary subunits, specific to mitochondrial complex I, form a shell around the core subunits, adding nearly 400kDa of proteins to the conserved subunits (Extended Data Fig. 6).…”
Section: General Descriptionsupporting
confidence: 61%
“…In plant, 25 proteins shared with aerobic yeast or mammals are present. Similarly to the previously obtained complex I structure 4,6,9,16 , the supernumerary subunits, specific to mitochondrial complex I, form a shell around the core subunits, adding nearly 400kDa of proteins to the conserved subunits (Extended Data Fig. 6).…”
Section: General Descriptionsupporting
confidence: 61%
“…The Q-chamber geometry and the free volume available to accommodate Q inside are similar among all determined active structures. [8][9][10][11]13 Although complex I has been cocrystallized with small Q analogs, 8,9 it is still unclear how natural substrates with long isoprenoid chains such as ubiquinone-10 in cyan and Nqo8 in pale green that form the Q-chamber with Q 10 colored in green and red alternating for each isoprenoid unit. Elements of secondary structure and residues (green sticks and pink spheres) discussed in the text are indicated.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray crystallographic structures of complex I from Thermus thermophilus (5) and Yarrowia lipolytica (6) were modeled at resolutions of 3.3 and 3.6 Å, respectively. The entire structures of mammalian complex I, including all 45 subunits (31 of which are the supernumerary subunits), from bovine (Bos taurus) (7,8), ovine (Ovis aries) (9), porcine (Sus scrofa domesticus) (10), and mouse (Mus musculus) (11) hearts and human (Homo sapiens) HEK293F cells (12) were modeled by single-particle cryoelectron microscopy (cryo-EM). One of the striking findings obtained with T. thermophilus complex I (5) is the identification of a long and narrow channel, which extends from the membrane interior to the Fe-S cluster N2 (ϳ30 Å long) and is a completely enclosed tunnel with only a narrow entry point (ϳ3 ϫ 5 Å diameter) for quinone/inhibitors; however, this has not yet been confirmed experimentally.…”
mentioning
confidence: 99%
“…From this, the yeast and ovine enzymes were supposed to be in the deactive state. Hirst and co-workers (8,11) recently reported that the structural changes accompanying deactivation may be common to the bovine and mouse enzymes. Considering the unusually long substrate-binding channel, definitions of how UQs of varying isoprenyl chain length (UQ 1 -UQ 10 ) enter and transit the channel to be reduced, thereby eliciting the same proton-pumping stoichiometry, remain elusive (13,14).…”
mentioning
confidence: 99%